Bioprospecting in Colombia (2013)
Despite the evolution of international policy on bioprospecting, Colombian regulations on the matter still lack uniformity with these international policies. Here we examine the effectiveness of Colombian policy on bioprospecting and its consonance with international guidelines and treaties. To this end, we requested information from the environmental authorities regarding study permits issued for scientific research on biodiversity and access granted to genetic resources. We also examined the number of research groups in Colombia registered under national directives. We found that scientific bioprospecting has increased in the last five years both in number of research groups (30%) and in the number of registered projects (8 times); however, the number of undertakings does not match the number of permits issued, suggesting a margin of informality (70%) in the execution of these activities. For the State to fulfill its duty and promote research in biodiversity, a change in policy must take place to remove the obstacles that hinder the legalization of scientific bioprospecting activities.